Factors shaping obstacles to task performance in the police force as seen by an employee - Iwona Czaplicka-Kozłowska; Andrzej Józef Kozłowski; Bogdan Nogalski (Journal of Modern Science, 2023)
Objectives Central and decentralized authorities influencing the functioning of uniformed services are usually guided by the principles set out in the programs of political parties. All this builds internal relations within the uniformed services and determines their functioning. These issues became the subject of research aimed at identifying obstacles that hinder the performance of tasks in the police formation.